Pengaruh model pembelajaran learning cycle 5e yang dipadu think pair share terhadap hasil belajar kognitif siswa kelas XI SMA Negeri Sidoarjo pada materi larutan penyangga - S. Luluk AN Nisak M; Fauziatul Fajaroh; Siti Marfu’ah (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
It is crucial that the concepts of buffer solutions must be properly understood by students. It is due to the fact that buffer solutions are closely related to daily life, for example in blood, drugs, and others. The results of research and interviews show that students' understanding and student learning outcomes about the buffer solution material is still low. A student-centered learning process is needed so that it can make the learning process more fun and improve students’ learning outcomes. A meaningful student-centered learning is needed for the Learning Cycle (LC) learning model. However, the group discussion on the 5E LC learning model was less patterned, so it was combined with a patterned cooperative learning model that is Think-Pair-Share (TPS). This study aims to see the implementation of the learning process from the classroom with 5E LC -TPS and 5E LC learning models, and the influence of the 5E LC-TPS on cognitive learning outcomes from the eleventh grade students of Sidoarjo on buffer solution material. The design of the study used in this study is a quasi-experimental design with post-test-only-control group design. The research finding showed that: (1) the implementation of the learning process of the two categorized classes was done very well that is 98.3 percent in the experimental class and 95.4 percent in the control class, (2) there is the influence of the 5E LC learning model combined by TPS on the cognitive learning outcomes of class students as indicated by the significant average differences of the two classes. The average value of cognitive learning outcomes of experimental class students is higher than the control class which is equal to 85.43 and the control class is 81.62. From the results of these studies it can be concluded that there is the influence of the 5E LC-TPS learning model on improving students' cognitive learning outcomes. Konsep-konsep larutan penyangga perlu dipahami siswa karena larutan penyangga erat kaitannya dengan kehidupan sehari-hari, misalnya penyangga karbonat dalam darah, obat-obatan, dan lain-lain. Hasil penelitian dan wawancara menunjukkan bahwa pemahaman siswa dan hasil belajar siswa tentang materi larutan penyangga masih rendah. Diperlukan suatu proses pembelajaran yang berpusat pada siswa sehingga dapat menjadikan proses pembelajaran lebih bermakana dan meningkatkan hasil belajar siswa. Salah satu pembelajaran bermakna yang berpusat pada siswa adalah model pembelajaran Learning Cycle (LC). Namun, diskusi kelompok pada model pembelajaran LC 5E kurang berpola, sehingga dipadukan dengan model pembelajaran kooperatif yang berpola yaitu Think Pair Share (TPS). Penelitian ini bertujuan untuk melihat keterlaksanaan proses pembelajaran dari kelas dengan model pembelajaran LC 5E-TPS dan LC 5E serta pengaruh model pembelajaran LC 5E -TPS terhadap hasil belajar kognitif siswa kelas XI SMA Negeri Sidoarjo pada materi larutan penyangga. Rancangan Penelitian yang digunakan dalam penelitian ini adalah rancangan eksperimental semu dengan post-test-only-control group design. Hasil penelitian menunjukkan bahwa: (1) keterlaksanaan proses pembelajaran kedua kelas terkategori terlaksana dengan sangat baik, yaitu 92,11 persen pada kelas eksperimen dan 90,78 persen pada kelas kontrol. (2) ada pengaruh model pembelajaran LC 5E yang dipadu TPS terhadap hasil belajar kognitif siswa kelas yang ditunjukkan oleh perbedaan rata-rata yang signifikan dari kedua kelas. Nilai rata-rata hasil belajar kognitif siswa kelas eksperimen lebih tinggi dari pada kelas kontrol yaitu sebesar 85,43 dan kelas kontrol sebesar 81,62. Dari hasil penelitian tersebut dapat disimpulkan bahwa ada pengaruh model pembelajaran LC 5E-TPS terhadap peningkatan hasil belajar kognitif siswa.